Contratos preliminares nas operações de compra e venda de participação acionária em companhias fechadas: requisitos para a celebração do contrato definitivo - Thaís Kleinsorge Mendes (2023)
This master thesis aims to deal with the criteria used to determine whether the parties, within the scope of an M&A transaction, are bound or not from the moment they enter a preliminary document, in other words, any draft that translates into a commitment by the parties to proceed with the transfer of the equity interest that constitutes the object of the intended transaction. Depending on what is contained in this document and the behavior manifested by the parties during the negotiation phase, as well as the particularities inherent to the purchase and sale in question, it could be said that the parties are bound, in an irreversible way, to get on with the business. If that is the case, the party that was injured by the non-consummation of the transaction could require the opposing party to be held liable in court. The proposed research is therefore part of an attempt to contribute to the discussions involving the requirements that oblige economic agents to proceed with the conclusion of a stock purchase agreement. This type of contract falls into the category of the atypical contracts and its execution is not instantaneous, which is why the task of identifying the different levels of binding assumed by the parties over the period that precedes the effective conclusion of the purchase and sale agreement becomes quite challenging. The work will address the process of forming business contracts and the principles that should guide the performance of economic agents in the so-called pre-contractual phase, but after the conclusion of a draft. Among these principles, a focus will be given to private autonomy, which finds its maximum expression in the freedom to contract, and to objective good faith, through the preservation of the principle of trust. In addition, in order to identify the arguments commonly used to defend the absence or presence of liability for breach of the pre-contract, the jurisprudential understandings given by the judges of the largest Brazilian courts will be addressed. Finally, the thesis will deal with the possible hypotheses of liability of the party that chooses to close negotiations involving a potential M&A transaction, aiming at a better adaptation to the peculiarities of the concrete case and in light of the terms and conditions set forth in the preliminary draft concluded.